Vein depth and diameter as predictive indicators of visibility and palpability during venipuncture in healthy volunteers - Miharu Matsumoto; Ayami Tateishi; Hiromitsu Kobayashi; Nobuko Hashiguchi (PLoS ONE, 2025)
Background The difficulty of venipuncture depends on the visibility and palpability of the vein and is particularly challenging in older adults, patients with abnormal body mass index, and those with chronic diseases. In these populations, vessel fibrosis, scarring, skin atrophy, and subcutaneous fat reduce vein visibility and palpability, making venous access more challenging. Previous studies have shown that visibility and palpability are associated with vein depth and diameter, respectively. The current study therefore aimed to evaluate the validity of vein depth and vein diameter as predictive indicators of vein visibility and palpability during venipuncture. Methods Three nurses evaluated the visibility and palpability of superficial veins suitable for venipuncture in 96 healthy volunteers who participated in this study. Using ultrasound imaging devices, the depth and diameter of superficial veins were measured, after which receiver operating characteristic (ROC) curves were created to identify the optimal cutoff values for predicting vein visibility and palpability. Results Both vein depth and diameter were found to be independent predictors of visibility and palpability (p < 0.05). ROC analysis showed that vein depth was a significant predictor of visibility (AUC = 0.901, 95% CI = 0.834–0.967) and palpability (AUC = 0.724, 95% CI = 0.619–0.829). The optimal cutoff values for vein depth were 1.89 mm for visibility discrimination, with 28.1% of veins exceeding this threshold, and 1.44 mm for palpability, with 59.4% of veins exceeding this threshold. On the other hand, vein diameter was less accurate than vein depth in predicting visibility and palpability (AUC < 0.7). Conclusions Vein depth is an effective predictor of vein visibility and vein palpability. This finding is expected to inform the development of assistive technology for visual and palpatory examinations.